The quality of life role in patients with locally advanced breast cancer in the comprehensive evaluation of the complex neoadjuvant treatment efficacy - Bondar, O. V.; Dzygal, O. F. (Journal of Education, Health and Sport, 2019)
In recent years, breast cancer has been the most common cancer and the most common cause of disability among women in developed countries. Determining the role of the quality of life parameter of patients during complex neoadjuvant treatment with the use of polychemotherapy in systemic (SPCT), endolymphatic (ELPCT) and selective intraarterial (SIAPCT) variants in patients with locally advanced breast cancer M. The study was conducted on the basis of materials from 526 cases of MR RMZ T4A-DN0-2M0. The total sample was divided into three subgroups by parameter of route of neoadjuvant polychemotherapy (PCT): first control group (22 patients) - SPCT; the second control group (27 patients) - ELPCT; study group (41 patients) - SIAPCT. Clinical effect with qualitative changes of local status and transfer of patients to the category of those with resectable tumors appeared in 46% of women of the first control group after 6 courses of SPCT, in 59% of the second control group after 4 courses of ELPHT and in 90% of the studied group after 3 courses SIAPCT. After 3 courses of PCT, statistically better results of the experimental group were obtained in the positive dynamics of quality of life index in the amplitude and chronometric complex logran study as a result of neoadjuvant SIAPCT compared with the first (p<0.001) and second (p<0.05) control groups. On the social well-being scale, the control group showed the best dynamics (p>0.05 inboth comparisons) with a high evaluation of restitution of work and social status. On the symptom scales in the third group, after each course of polychemotherapy, symptoms of nausea and loss of appetite were observed at a significantly lower intensity compared to both control groups within 15 - 25 points of the group (p<0.05 inboth comparisons) and lasted 1 - 2 days less ( p<0.05 inboth comparisons). Quality of life (QOL) research is a reliable, informative, and cost-effective method for assessing a patient's state of health at both group and individual levels. In cancer studies, QOL assessment is an important criterion for evaluating treatment effectiveness and is of prognostic value.